Production of potato seed tubers under the effect of Trichoderma sp. and rhizobacteria in greenhouse conditions (Revista de Ciências Agroveterinárias, 2022)
Potato (Solanum tuberosum L.) is one of the main crops in the Andean region and due to environmental aspects, the use of biocontrol agents is considered a safe way to produce potato seed tubers.The objective of the study was to evaluate potato inoculation with Trichoderma sp. as a matrix and rhizobacteria Bacillus simplex and Azotobacter sp. on the growth of potato seedlings from in vitro culture, for the production of seed tubers in a greenhouse. The inoculation of microorganisms was carried out in pots, using five potato genotypes for processing. The inoculation treatments were: control, Trichoderma sp., Trichoderma sp. + Azotobacter sp., Trichoderma sp. + Bacillus simplex, Trichoderma sp. + B. simplex + Azotobacter sp. The potato genotypes were cv. Unica (CIP392797.22), cv. Bicentenaria, the advanced clones CIP 396311.1, CIP 399101.1, and the experimental clone UH-09 from the Universidad Nacional José Faustino Sánchez Carrión. A completely randomized design was used, under a factorial arrangement and comparisons between treatments were made at p
Keywords: Trichoderma; Azotobacter; Bacillus; potato for processing; bacteria; fungi; plant tubers